Teaching educational projects-in biology teaching in a public school in the city of Porto Velho-RO - Nogueira, Patricia Guedes; Lima, Renato Abreu; Gomes, Daniele Bezerra; Monteiro, Vera Lúcia Guedes; Nogueira, Priscila Guedes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper argues for teaching biology projects executed in a public school in Porto Velho-RO, stressing the importance of seeking innovative strategies for teaching and learning, assuming that the teacher is rather able to motivate and overcome obstacles. Thus is described the methodology used to project implementation, the objectives to be achieved and the target audience. Explaining each stage thereof. Since the public schools in Brazil face daily challenges, it is concluded that the projects developed in the discipline of biology at the school to provide favorable conditions for student learning, creating an environment of stimulation, where the teacher is a key part of the motivation for these.